Death Criminal Concepts Based On Positive Law In Indonesia - Wahid, Abdul; Malarangan, Kartini (JURNAL LEGALITAS, 2022)
The existence of two opinions, especially capital punishment, has given rise to controversy over regulating the death penalty as a legal instrument for dealing with corruption. Some agree with the imposition of capital punishment, and some question the justification for this sentence, which does not give the perpetrators of criminal acts the opportunity to improve to become good human beings. The death penalty for corruption cases has never been imposed, so the death penalty cannot be used as an ultimum remedium against perpetrators of corruption. Regarding the severity of the main sentence to be charged, a maximum limit for each crime has been determined. In contrast, a specific minimum limit is not specified, but a general minimum limit, for example, imprisonment and a minimum of one day's confinement. This type of research is carried out using a normative approach, namely by analyzing problems through legal principles and referring to legal norms contained in statutory regulations. The results of the study show the need for amendments to the Law on the Eradication of Corruption Crimes by formulating the death penalty for all acts of corruption without particular criteria, such as disaster situations, due to their significant impact on society, the nation, and the State, so that it becomes the ultimum remedium. The need for judges to impose severe criminal sanctions to create a deterrent effect for corruptors and other people who have the opportunity to commit corruption to become reluctant or afraid to commit acts that violate the Law because the criminal sanctions are severe.